Cerebrovascular function in hypertension: Does high blood pressure make you old?. (24th August 2020) - Jennings, J. Richard; Muldoon, Matthew F.; Allen, Ben; Ginty, Annie T.; Gianaros, Peter J.
Abstract: The majority of individuals over an age of 60 have hypertension. Elevated blood pressure and older age are associated with very similar changes in brain structure and function. We review the parallel brain changes associated with increasing age and blood pressure. This review focuses on joint associations of aging and elevated blood pressure with neuropsychological function, regional cerebral blood flow responses to cognitive and metabolic challenges, white matter disruptions, grey matter volume, cortical thinning, and neurovascular coupling. Treatment of hypertension ameliorates many of these changes but fails to reverse them. Treatment of hypertension itself appears more successful with better initial brain function. We show evidence that sympathetic and renal influences known to increase blood pressure also impact brain integrity. Possible central mechanisms contributing to the course of hypertension and aging are then suggested. An emphasis is placed on psychologically relevant factors: stress, cardiovascular reactions to stress, and diet/obesity. The contribution of some of these factors to biological aging remains unclear and may provide a starting point for defining the independent and interacting effects of aging and increasing blood pressure on the brain. Impact Statement: Aging as a biological process has known negative impact on brain function and structure. We review results showing the very similar impact of hypertension. We know that hypertension is not a necessary consequence of aging. Hence, the review poses the question of how aging and hypertension interact to impact brain structure and function.